2022
DOI: 10.1101/2022.10.21.513224
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptomics reveals amygdala neuron regulation by fasting and ghrelin thereby promoting feeding

Abstract: SUMMARYThe central amygdala (CeA) consists of numerous genetically-defined inhibitory neurons that control defensive and appetitive behaviors including feeding. Transcriptomic signatures of cell types and their links to function remain poorly understood. Using single-nucleus RNA-sequencing, we describe nine CeA cell clusters, of which four are mostly associated with appetitive and two with aversive behaviors. To analyze the activation mechanism of appetitive CeA neurons, we characterized Serotonin receptor 2a … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 84 publications
3
20
0
Order By: Relevance
“…In addition to these major cell types, our study revealed additional cell-type diversity in the mouse CEA, especially in the CeM, which had been largely underdefined. In addition, our molecularly defined mouse CEA cluster also matched well with two recent studies in mouse CEA ( O’Leary et al, 2022 ; Peters et al, 2022 ; Figure 1—figure supplement 3 ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In addition to these major cell types, our study revealed additional cell-type diversity in the mouse CEA, especially in the CeM, which had been largely underdefined. In addition, our molecularly defined mouse CEA cluster also matched well with two recent studies in mouse CEA ( O’Leary et al, 2022 ; Peters et al, 2022 ; Figure 1—figure supplement 3 ).…”
Section: Discussionsupporting
confidence: 87%
“…In this study, we only analyzed samples from male animals, and additional experiments will be needed in female animals to evaluate whether there are differences in molecularly defined cell types or their projections. However, scRNA-seq data from Peters et al, 2022 using CEA neurons of both male and female animals did not report sex-specific differences. Ultimately, combining EASI-FISH with fluorescent retrograde tracers enables the profiling of tens of thousands of cells for gene expression and projections.…”
Section: Discussionmentioning
confidence: 91%
“…BLA Lypd1 neurons are found in three cell clusters in LA and acBA, complementary to BLA Etv1 neurons which are enriched in amBA and alBA. In slice electrophysiological recordings, BLA Lypd1 neurons showed increased firing rates in fasted animals, similar to our previous recordings of appetitive CeA neurons 57 . In vivo calcium recordings revealed that a large fraction of BLA Lypd1 neurons are active during food approach behavior, whereas smaller fractions of BLA Lypd1 neurons respond to fear and social stimuli.…”
Section: Discussionsupporting
confidence: 89%
“…The mechanism by which BLA Lypd1 neurons promote food intake remains to be explored. It is possible that BLA Lypd1 neurons directly synapse onto orexigenic CeA neurons including the recently described Ghrelin-responsive CeA Htr2a neurons 57 . It also remains to be tested whether the activity of BLA Lypd1 neurons is modulated by other internal states besides hunger and by environmental factors such a risk stimulus 35 .…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, 5HT2aR-expressing neurons in the central amygdala are responsive to fasting and modulate food consumption 47,48 . That HPCv 5HT2aR influence food intake through memory function is in line with reports in humans with Htr2a allele variants influencing hippocampal function [49][50][51] and work in rodents illustrating a role for 5HT2aR signaling in learning in memory processes [52][53][54][55][56][57] , and specifically in the HPCv 58 .…”
Section: Discussionmentioning
confidence: 99%